1) 5x-0,8=2x-1,4
5x-2x=-1,4+0,8
3x=-0,6п
x=-0,2
2)3x-2(3x-1)=2x+7
3x-(2×3x-2×1)=2x+7
3x-6x+2=2x+7
3x-6x-2x=7-2
-5x=5
x=-1
3)(2x:5=(x-3):7)×35
14x=5x-15
14x-5x=-15
9x=-15
x=-1целая две третих
❤️
Объяснение:
5х - 0,8 = 2х - 1,4
5х - 2х = 1,4 + 0,8
3х = - 0,6
х = - 0,2
1) 5x-0,8=2x-1,4
5x-2x=-1,4+0,8
3x=-0,6п
x=-0,2
2)3x-2(3x-1)=2x+7
3x-(2×3x-2×1)=2x+7
3x-6x+2=2x+7
3x-6x-2x=7-2
-5x=5
x=-1
3)(2x:5=(x-3):7)×35
14x=5x-15
14x-5x=-15
9x=-15
x=-1целая две третих
❤️
Объяснение:
5х - 0,8 = 2х - 1,4
5х - 2х = 1,4 + 0,8
3х = - 0,6
х = - 0,2